Exploring the influence of media dependency, perspective taking, meaning in life, and psychological capital on online prosocial behavior among Malaysian public university students - Tongbin, Luo; Ma’rof, Aini Azeqa; Zaremohzzabieh, Zeinab (Human Resource Management Academic Research Society, 2024)
This study investigates the relationships between media dependency, perspective-taking, meaning in life, and psychological capital in predicting online prosocial behavior among Malaysian public university students. A sample of 425 students was analyzed using Pearson correlation and multiple regression to examine how these factors contribute to prosocial actions in digital spaces. Results revealed that psychological capital was the strongest predictor of online prosocial behavior, followed by meaning in life, perspective-taking, and media dependency. Psychological resources, such as self-efficacy, optimism, and resilience, significantly enhance students' likelihood to engage in prosocial actions online, while having a sense of meaning and empathy further supports positive online interactions. Media dependency, though influential, had a weaker effect, suggesting that the quality of media engagement moderates its impact on prosocial behavior. These findings highlight the importance of fostering psychological resilience, purpose, and empathy in educational programs to promote prosocial engagement in digital environments. Policymakers and educators are encouraged to implement initiatives that develop these psychological and social factors to enhance positive online behavior among university students.